1991
DOI: 10.1042/bj2740607
|View full text |Cite
|
Sign up to set email alerts
|

c-myc mRNA in cytoskeletal-bound polysomes in fibroblasts

Abstract: 3T3 fibroblasts were treated sequentially with 25 mM-KCl/0.05% Nonidet P40, 130 mM-KCl/0.05% Nonidet P40 and finally with 1% Nonidet P40/1% deoxycholate in order to release free, cytoskeletal-bound and membrane-bound polysomes respectively. The membrane-bound fraction was enriched in the mRNA for the membrane protein beta 2-microglobulin, whereas the cytoskeletal-bound polysomes were enriched in c-myc mRNA. Actin mRNA was present in both free and cytoskeletal-bound polysomes. The results suggest that cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 19 publications
(19 reference statements)
4
40
0
Order By: Relevance
“…As shown in Fig. 1, results from 3T3 fibroblasts (Hesketh et al, 1991b) have shown the Vol. 277 7 presence of mRNA for actin both in FP and CBP in roughly equal concentrations but that in terms of overall quantities some 600% of the actin mRNA was found in the cytoskeletal-bound fraction.…”
Section: Physiological Significance Of Cytoskeletal-bound Polysomes Tmentioning
confidence: 76%
See 3 more Smart Citations
“…As shown in Fig. 1, results from 3T3 fibroblasts (Hesketh et al, 1991b) have shown the Vol. 277 7 presence of mRNA for actin both in FP and CBP in roughly equal concentrations but that in terms of overall quantities some 600% of the actin mRNA was found in the cytoskeletal-bound fraction.…”
Section: Physiological Significance Of Cytoskeletal-bound Polysomes Tmentioning
confidence: 76%
“…actively translated, mRNA from the cell matrix (Lenk & Penman, 1979). Further evidence for the presence of specific mRNA species on the cytoskeleton has come from work in which fractions enriched in cytoskeletal components have been prepared from the cell matrix and shown to be highly enriched in mRNA coding for either Vgl (Pondel & King, 1988) or c-myc (Hesketh et al, 1991b; Fig. 1).…”
Section: Association Of Initiation Factors and Mrnas With The Cytoskementioning
confidence: 99%
See 2 more Smart Citations
“…For example, in neurons and oligodendroglia, some mRNAs are transported over considerable subcellular distances (Shan et al 2003), and in fibroblasts, transcripts encoding b-actin and creatine kinase isoform M are transported to the cell periphery (Kislauskis et al 1993;Wilson et al 1995), whereas, in contrast, c-myc, c-fos, Metallothionein-1 (MT-1), and vimentin mRNAs remain localized to the perinuclear cytoplasm Mahon et al 1997;Zehner et al 1997;Dalgleish et al 2001). The mRNAs localized around the nucleus, including MT-1 mRNA, are associated with cytoskeletal-bound polysomes or the cytoskeleton itself (Hesketh et al 1991;Mahon et al 1997;Dalgleish et al 2001). In the case of MT-1, perinuclear localization of the mRNA has been shown to be required for subsequent import of the protein into the nucleus during the G1/S transition and for the ability of MT-1 to protect cells from DNA damage (Levadoux et al 1999;Levadoux-Martin et al 2001).…”
Section: Introductionmentioning
confidence: 99%